Entrepreneurship and cultural creativity - Michael Fritsch; Alina Rusakova (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
We investigate the relationship between cultural creativity and entrepreneurship in two respects: first, cultural and personal creativity as a characteristic of self-employed individuals; second, selfemployment in professions that can be classified as belonging to the 'Creative Class' as compared to the non-creative class. The analysis is based on micro-data for individuals of the German Socio Economic Panel (SOEP). We find, indeed, some significant links between entrepreneurship and cultural creativity that deserve further investigation.
Keywords: L26; Z1; D03; 330; Entrepreneurship; new business formation; cultural creativity; creative class; Unternehmer; Unternehmensgründung; Selbstständige; Kreativität; Persönlichkeitspsychologie; Deutschland